Exercise but not methacholine differentiates asthma from chronic lung disease in children. Issue 7 (July 1991) - Godfrey, S; Springer, C; Noviski, N; Maayan, C; Avital, A
Abstract : Bronchial provocation challenges with exercise and methacholine were performed on the same day or within a short interval in 52 children with asthma, 22 with other types of chronic lung disease (including cystic fibrosis), and 19 control subjects with no evidence of chronic lung disease. There were no significant differences in the baseline lung function before the two types of challenge in the individual groups and differences between the patients with asthma and with chronic lung disease were minor. When the mean -2 SD of the methacholine response of the control group was taken as the lower limit of normal, 49/52 (94%) patients with asthma and 18/22 (82%) with chronic lung disease responded abnormally. In contrast, with the mean +2 SD of the exercise response of the control group as the upper limit of normal, 41/52 (79%) asthmatic patients responded but none of those with chronic lung disease. Thus the response to the two types of challenge helps to distinguish asthma from other types of chronic lung disease in children.